Efficient FEM-DBEM coupled approach for crack propagation simulations. (October 2017) - Giannella, V.; Perrella, M.; Citarella, R.
Highlights: An efficient FEM-DBEM procedure is proposed for crack propagation simulations. The procedure is based on the principle of linear superposition. SIFs are computed with high accuracy by a simple DBEM stress analysis. Results are validated by comparison with those obtained with a different approach. The approach is automated and SIFs are evaluated with reduced computational effort. Abstract: The paper deals with a FEM-DBEM hybrid methodology applied to crack propagation simulations. The method allows to simulate cracks propagation by means of Finite Element Method (FEM) and Dual Boundary Element Method (DBEM), coupled in a procedure that optimise computational effort and accuracy. FEM is used for stress evaluation of the uncracked domain, whereas, the fracture analysis on a submodel embedding the cracked zone is demanded to DBEM. In particular, a DBEM submodel is extracted from the FEM model, a crack is introduced and traction boundary conditions are transferred from global FEM analysis to the crack surfaces of DBEM submodel (this will result the only needed boundary conditions to work out the DBEM analysis). The aforementioned tractions are those corresponding to the stresses calculated by a FEM global analysis along the virtual path traced by the DBEM advancing crack; consequently, a continuous exchange of data between FEM and DBEM environments is needed during the step by step crack propagation simulation. The proposed case study is based on a shaft/hub coupling undergoing three different loading conditions: combined "bending" and "press-fit", "shear" and "torque". The material is a common steel with isotropic mechanical properties, whose Paris' parameters are calibrated at room temperature. J -integral and Minimum Strain Energy Density (MSED) methods are chosen for Stress Intensity Factors (SIFs) and crack path assessment respectively. A sound agreement is shown among SIFs calculated with the proposed Loaded Crack (LC) method and those evaluated by a "classical" FEM-DBEM approach, where displacement or traction boundary conditions, again retrieved from a FEM analysis of the uncracked global model, are applied on all DBEM submodel cut surfaces.